Ekstraksi Bunga Telang dan Bawang Dayak Sebagai Pewarna Alami dan Antioksidan Pada Kue Mangkuk - Manurung, Hotman; Tampubolon, Jongkers; Tindaon, Ferisman; Naibaho, Dunan; Simbolon, Shanti Desima (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
The two main challenges to food security in Indonesia relate to the availability and safety of food, in the sense that hazardous materials do not contaminate it. Availability can be overcome with semi-subsistence measures, i.e., people produce some of their food for household needs by utilizing the home-yard to reduce expenditure. Meanwhile, safe food can be obtained by avoiding additives/synthesized ingredients and replacing them with natural ingredients. The community service (PKM) aims to socialize utilizing home-yard, healthy food, and natural coloring ingredients that contain antioxidants when making cupcakes. The coloring material was extracted from telang flower and dayak onion, which are local weeds. The PKM results showed that 80% of participants were motivated to utilize their home-yard to grow food, and 53% were motivated to raise livestock and fish. Healthy food socialization improved the understanding of all participants (100%) on the concept of nutritious, balanced, healthy, and safe food (B2SA) as an improvement on the old idea of four healthy, five perfect. All participants (100%) stated that they intend to make their cupcakes at home after seeing that making them is not difficult, the equipment is simple, the ingredients are not expensive, and the time required is not much.